Beyond “pancakes for breakfast” - assessing Cultural awareness in the EFL classroom - Albuquerque, Ana (2023)
Culture is an inseparable part of language and has always played a role the EFL classroom, however, perspectives on how to deal with the cultural aspects of the foreign language differ among teachers and researchers. On the other hand, in the globalized internet world we live in today, further issues arise concerning which aspects of culture should be brought into the classroom to enhance students’ awareness of the anglophone cultures they may engage with in their professional and personal lives. Drawing from Hymes notion of communicative competence (1972) and Moran’s “five elements of culture” (2001), the study focuses on the notion that, although embedded in language, the teaching of the target culture requires explicit approaches and teaching strategies, which should go beyond the surface-level information about “pancakes for breakfast” or “talking about the weather.” According to Gonzalez (2018): “Moran explains that culture learning outcomes can be varied and can tackle different learner’s needs,” however teachers are not always aware of such needs or how to address them in class. Ultimately aiming at clarifying the purpose of incorporating culture into language instruction in the current globalized world, the study uses questionnaires to analyze teachers and learners perspectives of culture in EFL teaching and learning in the era of globalization. The survey will be administered to a small community of teachers and students at a higher education institution and, hopefully, it will bring light into how the teaching of culture should integrate EFL courses and syllabi in the future.